HUBUNGAN TUNDAAN DAN PANJANG ANTRIAN TERHADAP KONSUMSI BAHAN BAKAR MINYAK PADA PENDEKAT SIMPANG (STUDI KASUS SIMPANG ANTASARI, SIMPANG AIR PUTIH, SIMPANG LEMBUSWANA DAN SIMPANG AHMAD YANI) - AHRYS, VALENTINO (KURVA S JURNAL MAHASISWA, 2017)
Petroleum Fuel (BBM) is one of the most limited natural resources and can not be renewed, thus making its availability become scarce as time passes and increasing energy demand especially in the field of transportation. Increasing the number of motor vehicles causes the increasing consumption of fuel oil (BBM) for motor vehicle energy. The condition of the vehicle stops (idle) due to a signal intersection resulting in fuel oil (BBM) wasted. So that the analysis of fuel consumption (BBM) is wasted when the vehicle stops (idle) due to a signal intersection need to be investigated. This study aims to determine the relationship between delay and queue length of fuel consumption due to a signal intersection in the city of Samarinda. Primary survey conducted in this study in the form of vehicle volume, length of delay and length of queue at intersection. Fuel consumption based on long delay using the equation at idle of LAPI-ITB. The delay relationship and the length of queue with the fuel consumption using linear regression analysis, with the value of fuel consumption (Ŷ, liter) as dependent variable influenced by the free variable is delay (X1, sec) and queue length (X2, meter). Intersection of antasari, intersection of air putih, intersection of lembuswana and intersection of ahmad yani, is the predominant alignment in Samarinda city because not only pass by vehicle in Samarinda city but also pass by vehicle coming from Balikpapan to Bontang, thus increasing the number of vehicles in town Samarinda and cause long queue.                 The method used for data retrieval of the number of vehicles, length of delay and length of queue using LHR, stopwatch and meter are carried out in the field. While the data analysis method using SPSS 23 software.                 From the analysis results can be concluded significantly that, the length of the queue and the length of delay greatly affect the fuel consumption at the tested intersection that has been tested.